Underutilised food species database with nutrition data, common and local names, medicinal uses and links to recipes - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
The database is online along with a growing global online repository of information on biodiversity for food and nutrition. Researchers from Bioversity International and other partners monitor use with Google Analytics. A recent publication (https://www.mdpi.com/2073-4395/10/2/231/htm) highlights further applications in research and policy.